High Prevalence of Strongyloides among South Asian Migrants in Primary Care―Associations with Eosinophilia and Gastrointestinal Symptoms - Elinor Chloe Baker; Damien K. Ming; Yasmin Choudhury; Shahedur Rahman; Philip J. Smith; Jose Muñoz; Peter L. Chiodini; Chris J. Griffiths; Christopher J. M. Whitty; Michael Brown (Pathogens, 2020)
Gastrointestinal (GI) symptoms are a frequent reason for primary care consultation, and common amongst patients with strongyloidiasis. We conducted a prospective cohort and nested case control study in East London to examine the predictive value of a raised eosinophil count or of GI symptoms, for Strongyloides infection in South Asian migrants. We included 503 patients in the final analyses and all underwent a standardised GI symptom questionnaire, eosinophil count and Strongyloides serology testing. Positive Strongyloides serology was found in 33.6% in the eosinophilia cohort against 12.5% in the phlebotomy controls, with adjusted odds ratio of 3.54 (95% CI 1.88−6.67). In the GI symptoms cohort, 16.4% were seropositive but this was not significantly different compared with controls, nor were there associations between particular symptoms and Strongyloidiasis. Almost a third (35/115) of patients with a positive Strongyloides serology did not have eosinophilia at time of testing. Median eosinophil count declined post-treatment from 0.5 cells × 109/L (IQR 0.3−0.7) to 0.3 (0.1−0.5), p < 0.001. We conclude Strongyloides infection is common in this setting, and the true symptom burden remains unclear. Availability of ivermectin in primary care would improve access to treatment. Further work should clarify cost-effectiveness of screening strategies for Strongyloides infection in UK migrant populations.